BfmRS encodes a regulatory system involved in light signal transduction modulating motility and desiccation tolerance in the human pathogen Acinetobacter baumannii - Perez Mora, Barbara Edith (2022)
We have previously shown that Acinetobacter baumannii as well as other relevant clinical bacterial pathogens such as Staphylococcus aureus and Pseudomonas aeruginosa, perceive and respond to light at 37 °C, the normal temperature in mammal hosts. In this work, we present evidence indicating that the two-component system BfmRS transduces a light signal in A. baumannii at this temperature, showing selective involvement of the BfmR and BfmS components depending on the specific cellular process. In fact, both BfmR and BfmS participate in modulation of motility by light, while only BfmR is involved in light regulation of desiccation tolerance in this microorganism. Neither BfmR nor BfmS contain a photoreceptor domain and then most likely, the system is sensing light indirectly. Intriguingly, this system inhibits blsA expression at 37 °C, suggesting antagonistic functioning of both signaling systems. Furthermore, we present evidence indicating that the phosphorylatable form of BfmR represses motility. Overall, we provide experimental evidence on a new biological function of this multifaceted system that broadens our understanding of A. baumannii’s physiology and responses to light.